Interleukin-4 Promotes Myogenesis and Boosts Myocyte Insulin Efficacy - Chang, Yih-Hsin; Tsai, Jen-Ning; Chen, Tzu-Lin; Ho, Kuo-Ting; Cheng, Hsin-Yi; Hsiao, Chiao-Wan; Shiau, Ming-Yuh (Mediators of Inflammation, 2019)
Anti-inflammatory cytokine interleukin-4 (IL-4) promotes glucose tolerance and insulin sensitivity while reduces lipid deposits. However, the effects of IL-4 on energy metabolism in muscle, the largest insulin-targeting organ, remain obscure. The study aimed at addressing the roles of IL-4 in myocyte differentiation (myogenesis) and energy metabolism of muscle cells. Effects of IL-4 on myogenesis, and interaction between IL-4 and insulin on glucose metabolism of C2C12 myoblasts and the terminal differentiated myocytes were analyzed. IL-4 improved GLUT4 translocation and tended to elevate glucose uptake by boosting insulin signaling. In diabetic mice, transient and long-term IL-4 showed differential effects on insulin signaling and efficacy. The study provides evidence to address the roles of IL-4 in mediating whole-body muscle reservoir and glucose metabolism, as well as the interaction between immune responses and energy homeostasis. IL-4 has dual potential to act as an adjuvant therapeutic target for sarcopenia to preserve muscle mass and insulin resistance to improve insulin sensitivity, which implicates the regulation of immune system to the muscle differentiation and exercise performance.